Zinc and nickel adsorption onto a low-cost mineral adsorbent: kinetic, isotherm, and thermodynamic studies. Issue 46 (1st October 2016) - Emami, Arman; Rahbar-Kelishami, Ahmad
Abstract: In this study, adsorption of zinc and nickel ions from aqueous solutions by low-cost dolomite was investigated. Dolomite, as a mineral adsorbent, is ample in most countries of the world. Morphology of adsorbent surface and the nature of the dolomite powder were examined using the scanning electron microscope. The process has been studied as a function of contact time, pH, initial concentrations, temperature, and adsorbent dosage. The experimental data were evaluated using three isotherm and kinetic models, including the pseudo-first-order, pseudo-second-order, and intraparticle diffusion models for kinetics and Freundlich, Langmuir and Temkin for isotherms. The results showed that the adsorption isotherm data were fitted well by the Langmuir isotherm and adsorption kinetics followed the pseudo-second-order model for both metal ions. The thermodynamic parameters, such as the change in standard free energy, enthalpy, and entropy, were also determined. The calculated parameters indicated that adsorption process was spontaneous and endothermic in nature. The adsorption capacity of zinc and nickel onto dolomite powder found to be 21.85 and 20.09 mg/g, respectively.